Iван Васильович Сименог (до 75-рiччя вiд дня народження) - Zagorodny, A. G.; Loktev, V. M.; Lev, B. I.; Petrov, E. G.; Belyaev, V. B.; Gavrylyk, O. M.; Grinyuk, B. E.; Zasenko, V. I.; Motovilov, A. K.; Yakovlev, S. L. (Publishing house "Academperiodika", 2018)
-